An agile approach to co-creation of the curriculum - Owen, John; Wasiuk, Catherine (International Journal for Students as Partners, 2021)
The importance of developing meaningful student engagement through partnerships is an increasing area of interest and practice within the context of learning and teaching in higher education. This case study reports on an approach used in a co-created curriculum project that aligned the values and principles of student-staff partnerships with those of an agile framework. Through an analysis of the individual team reflections captured during and after the project, the study explores how the agile approach could help address imbalances of power between students and staff in higher education. The results of the study show that team members found that working in this new way increased confidence in co-creating teaching and learning with staff and fostered a positive team relationship, although some reflections indicate that assumptions of power are deeply embedded within the structures and roles of higher education. However, our findings suggest that this way of working can result in positive experiences for students and staff and could be applied to a wide range of student-staff partnership projects.